Oil-stain-resistant aluminum oxide ceramic membrane for filtering special gas and preparation method thereof

By uniformly wrapping nano titanium oxide particles on the alumina ceramic membrane and adopting microwave low-temperature sintering technology to form a specific microstructure, the problem of the flux reduction and structural damage when dealing with oily and dirty gas is solved, and the resistance is significantly improved Oil pollution performance and stability of gas filtration flux.

CN119215684APending Publication Date: 2024-12-31SUNTAR MEMBRANE TECHNOLOGY (XIAMEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411246189.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The flux of the alumina ceramic membrane drops rapidly when treating oil-containing gases, and the accumulation of oil-containing gases leads to channel blockage and chemical reactions, affecting the membrane performance and structure.

Method used

The nanotitanium oxide particles are uniformly wrapped in the surface and internal cracks of alumina ceramic particles by high pressure hydrothermal method. Through microwave low-temperature sintering technology, combined with the high absorption efficiency of nanotitanium oxide, a specific microstructure is formed to reduce the adhesion point of oil stains. .

Benefits of technology

It significantly improves the anti-oil performance of ceramic membranes, avoids flux reduction and chemical reactions, and ensures the stability of gas filtration flux and the integrity of membrane structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215684A_ABST
    Figure CN119215684A_ABST
Patent Text Reader

Abstract

The invention discloses an oil-stain-resistant special gas filtering aluminum oxide ceramic membrane and a preparation method thereof.The preparation method includes the steps that firstly, a high-pressure hydrothermal method is adopted, the surfaces of aluminum oxide ceramic particles are evenly wrapped with nano particles, and crack defects in the particles are filled; then, by adopting a microwave low-temperature rapid one-time sintering technology, by utilizing a uniform and rapid heating mode and combining the high wave-absorbing efficiency of the nano titanium oxide particles (the efficiency is superior to that of the large-particle alpha-aluminum oxide), the nano titanium oxide particles are stably and rapidly combined into cracks on the surface of the large-particle aluminum oxide ceramic powder and in the particles. According to the method, the problems of desorption, agglomeration and segregation of nano-particles possibly occurring in the subsequent ball milling, film coating and sintering processes are effectively avoided, so that the defects and non-uniformity of the ceramic film support body are reduced. Meanwhile, compared with a traditional heating method, more uniform temperature distribution is achieved through microwave heating, and abnormal agglomeration and growth of nanocrystals are prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic membrane preparation, and in particular relates to an oil-resistant special gas filtering alumina ceramic membrane and a preparation method thereof. Background Art

[0002] Specialty gas filtration ceramic membranes are key materials for the filtration and purification of electronic specialty gases, and play a vital role in the semiconductor manufacturing process. These ceramic membranes must have extremely high purity and cleanliness to ensure the quality and performance of electronic specialty gases, and thus the quality and reliability of semiconductor devices. In semiconductor manufacturing, the main function of electronic specialty gas filtration ceramic membranes is to remove particles, moisture and other potential contaminants from the gas. If these contaminants are not effectively removed, it may cause the performance of semiconductor devices to deteriorate, or even cause the entire production batch to be scrapped.

[0003] Alumina ceramic membrane is a high-performance membrane material widely used in gas filtration and separation. Its high temperature resistance, chemical corrosion resistance and mechanical strength play an important role in the separation process of various industrial gases. However, when treating gases containing oil contamination, alumina ceramic membranes often encounter the problem of rapid flux decline. Oil contamination usually refers to oil droplets or oil vapor in the gas. These oil molecules or particles may accumulate on the membrane surface or in the pores. The components of oil contamination may include lubricating oil, fuel oil, synthetic oil, etc., which have strong adhesion and high molecular weight. During the gas filtration process, the oil contamination first forms an oil film on the surface of the alumina ceramic membrane, which directly affects the gas flux of the membrane because the oil film hinders the passage of gas molecules and reduces the permeability of the membrane (such as Figure 1 shown).

[0004] Oil molecules sometimes enter the pores of the membrane, causing the oil droplets to aggregate and clog the pores, reducing the effective filtration area of ​​the membrane and significantly reducing the amount of gas passing through. Long-term oil deposition may cause changes in the membrane pore size, and deposition may cause the membrane pore size to shrink, affecting the separation performance and flux of the membrane. In addition, some oil components may react chemically with the membrane material under high temperature conditions, causing changes in the chemical properties of the membrane surface. This chemical reaction may further reduce the permeability of the membrane and may cause damage to the membrane structure. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide an oil-resistant special gas filtering alumina ceramic membrane and a preparation method thereof.

[0006] The technical solution of the present invention is as follows:

[0007] An oil-resistant special gas filtering alumina ceramic membrane and a preparation method thereof, comprising the following steps:

[0008] (1) mixing an alumina ceramic powder having an average particle size of 300-800 nm with a nano-titanium oxide dispersion having a concentration of 12-15 wt%, and reacting the mixture under high pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 h, wherein the average particle size of the nano-titanium oxide in the nano-titanium oxide dispersion is 5-20 nm;

[0009] (2) drying the material obtained in step (1), and then performing low-temperature sintering at 420-430° C. for 25-35 min using a microwave heating device to obtain titanium oxide-coated aluminum oxide powder;

[0010] (3) ball-milling and mixing the titanium oxide-coated alumina powder obtained in step (2), PVA with an average particle size of 0.8-1.2 μm, RO water, a polysiloxane defoamer and a methyl cellulose thickener;

[0011] (4) coating the material obtained in step (3) on hydrophilically modified oil-resistant gas filtration alumina to obtain a wet blank;

[0012] (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1150-1450° C. for 3-5 hours to obtain the oil-resistant special gas filtration alumina ceramic membrane.

[0013] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%.

[0014] In a preferred embodiment of the present invention, the drying temperature in step (2) is 120° C. and the drying time is 4 hours.

[0015] In a preferred embodiment of the present invention, in step (3), the ratio of titanium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 20-25wt%: 2.5-3wt%: 70-76wt%: 0.01-0.03%: 0.98-1.99wt%.

[0016] Further preferably, in step (3), the average particle size of the PVA is 1 μm.

[0017] In a preferred embodiment of the present invention, in the step (4), the shade drying time is 4 hours.

[0018] In a preferred embodiment of the present invention, in the step (4), the drying temperature is 105° C. and the drying time is 2 h.

[0019] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%; in the step (3), the ratio of titanium oxide-coated alumina powder, PVA, RO water, polysilicone defoamer and methyl cellulose thickener is 20-25wt%: 2.5-3wt%: 70-76wt%: 0.01-0.03%: 0.98-1.99wt%.

[0020] Further preferably, in step (3), the average particle size of the PVA is 1 μm.

[0021] More preferably, in step (4), the shade drying time is 4 hours; the drying temperature is 105° C. and the drying time is 2 hours.

[0022] The beneficial effects of the present invention are:

[0023] 1. The present invention firstly adopts a high-pressure hydrothermal method to uniformly wrap nanoparticles on the surface of alumina ceramic particles and fill the crack defects inside the particles; then, a microwave low-temperature rapid one-time sintering technology is adopted, and the nano-titanium oxide particles are stably and rapidly combined with the surface of large-particle alumina ceramic powder and the cracks inside the particles by using a uniform and rapid heating method and the high wave absorption efficiency of nano-titanium oxide particles (this efficiency is better than that of large-particle α-alumina); this effectively avoids the problems of nano-particle desorption, agglomeration and segregation that may occur during subsequent ball milling, coating and sintering, thereby reducing the defects and non-uniformity of the ceramic film support. At the same time, compared with the traditional heating method, the microwave heating in the present invention achieves a more uniform temperature distribution and prevents the abnormal agglomeration and growth of nano-crystals.

[0024] 2. The introduction of nano titanium oxide particles in the present invention not only improves the overall oleophobicity of the gas filtration membrane layer, but also forms specific microstructures or nanostructures on the membrane surface. These microstructures effectively reduce the attachment points of oil stains and reduce the accumulation of oil stains.

[0025] 3. The oil-resistant special gas filtration alumina ceramic membrane prepared by the present invention has achieved a qualitative leap in anti-oil performance, effectively solving the problem of rapid flux decline of existing special gas filtration alumina ceramic membranes when treating oil-containing gases, avoiding the influence of oil on membrane separation performance and the possible changes in chemical properties and structural damage on the membrane surface, and providing strong technical guarantee for the large-scale application and promotion of special gas filtration ceramic membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a surface electron microscope photograph of the alumina ceramic membrane in the background technology of the present invention after filtering oil pollution.

[0027] Figure 2 This is a surface electron microscope photograph of the oil-resistant special gas filtering alumina ceramic membrane prepared in Example 1 of the present invention after filtering oil. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.

[0029] Example 1

[0030] (1) Alumina ceramic powder (Al2O3 purity> 99.9%, average particle size 800nm) and nano-titanium oxide dispersion (concentration of 15wt%, wherein the purity of TiO2 is> 99.9%, average particle size 20nm) were mixed and reacted under high pressure (8MPa) hydrothermal (300℃) conditions for 4h;

[0031] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 430° C. for 30 min using a microwave heating device to obtain titanium oxide-coated aluminum oxide powder;

[0032] (3) The titanium oxide-coated alumina powder, PVA (average particle size of 1 μm), RO water and an appropriate amount of polysiloxane defoamer + methyl cellulose thickener obtained in step (2) are ball milled for 4 hours, wherein the ratio of titanium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 25wt%: 3wt%: 70wt%: 0.01%: 1.99wt%.

[0033] (4) coating the material obtained in step (3) on a hydrophilically modified oil-resistant gas filtration alumina support to obtain a wet blank.

[0034] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 4 hours, then slowly heated to 105° C. in an oven for drying for 2 hours, and then sintered at 1450° C. in a high-temperature sintering electric kiln for 4 hours to obtain the oil-resistant special gas filtration alumina ceramic membrane (the surface morphology after filtering the oil is as follows Figure 2 As shown, the introduction of nano-titanium oxide particles not only improves the overall oleophobicity of the gas filtration membrane layer, but also forms specific microstructures or nanostructures on the membrane surface. These microstructures effectively reduce the attachment points of oil stains and reduce the accumulation of oil stains).

[0035] After testing, the performance of the oil-resistant special gas filtration alumina ceramic membrane is: when treating gas containing 0.5wt% oil (gas temperature 65°C, inlet pressure 0.2MPa), the gas filtration flux can be stably maintained at 210SLPM. In contrast, when the ceramic membrane made by simple mechanical mixing of the same raw materials is used to treat gas containing 0.5wt% oil, the gas filtration flux can only be maintained at 60SLPM in the initial stage under the same test conditions.

[0036] Example 2

[0037] (1) Alumina ceramic powder (Al2O3 purity> 99.9%, average particle size 300nm) and nano-titanium oxide dispersion (concentration of 12wt%, wherein the purity of TiO2 is> 99.9%, average particle size 5nm) were mixed and reacted under high pressure (16MPa) hydrothermal (350℃) conditions for 4h;

[0038] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 430° C. for 30 min using a microwave heating device to obtain titanium oxide-coated aluminum oxide powder;

[0039] (3) The titanium oxide-coated alumina powder, PVA (average particle size of 1 μm), RO water and an appropriate amount of polysiloxane defoamer + methyl cellulose thickener obtained in step (2) are ball-milled for 4 hours using a ball mill, wherein the ratio of titanium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 20wt%: 3wt%: 76wt%: 0.02%: 0.98wt%.

[0040] (4) coating the material obtained in step (3) on hydrophilically modified oil-resistant gas filtration alumina to obtain a wet blank.

[0041] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 4 hours, then slowly heated to 105°C in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering at 1150°C in a high-temperature sintering electric kiln for 4 hours to obtain the oil-resistant special gas filtration alumina ceramic membrane (the surface morphology after filtering the oil is basically the same as that in Example 1).

[0042] After testing, the performance of the oil-resistant special gas filtration alumina ceramic membrane is: when treating gas containing 0.5wt% oil (gas temperature 65°C, inlet pressure 0.2MPa), the gas filtration flux can be stably maintained at 290SLPM. In contrast, when the ceramic membrane made by simple mechanical mixing of the same raw materials is used to treat gas containing 0.5wt% oil, the gas filtration flux can only be maintained at 100SLPM in the initial stage under the same test conditions.

[0043] Example 3

[0044] (1) Alumina ceramic powder (Al2O3 purity> 99.9%, average particle size 600nm) and nano-titanium oxide dispersion (concentration of 15wt%, wherein the purity of TiO2 is> 99.9%, average particle size 5nm) were mixed and reacted under high pressure (13MPa) hydrothermal (335℃) conditions for 4h;

[0045] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 430° C. for 30 min using a microwave heating device to obtain titanium oxide-coated aluminum oxide powder;

[0046] (3) The titanium oxide-coated alumina powder, PVA (average particle size of 1 μm), RO water and an appropriate amount of polysiloxane defoamer + methyl cellulose thickener obtained in step (2) are ball-milled for 4 hours using a ball mill, wherein the ratio of titanium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 23wt%: 2.5wt%: 73wt%: 0.03%: 1.47wt%.

[0047] (4) coating the material obtained in step (3) on hydrophilically modified oil-resistant gas filtration alumina to obtain a wet blank.

[0048] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 4 hours, then slowly heated to 105°C in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering at 1350°C in a high-temperature sintering electric kiln for 4 hours to obtain the oil-resistant special gas filtration alumina ceramic membrane (the surface morphology after filtering the oil is basically the same as that in Example 1).

[0049] After testing, the performance of the oil-resistant special gas filtration alumina ceramic membrane is: when treating gas containing 0.5wt% oil (gas temperature 65°C, inlet pressure 0.2MPa), the gas filtration flux can be stably maintained at 250SLPM. In comparison, when the ceramic membrane made by simple mechanical mixing of the same raw materials is used to treat gas containing 0.5wt% oil, the gas filtration flux can only be maintained at 80SLPM in the initial stage under the same test conditions.

[0050] According to the above examples, the ceramic membrane prepared in the present invention can stably maintain a gas filtration flux of 200-300 SLPM when treating gas containing 0.5 wt% oil. In contrast, the gas filtration flux of the alumina ceramic membrane for gas filtration without nano-titanium oxide modification can only be maintained at 50-100 SLPM in the initial stage under the same conditions, and after a period of operation, due to the serious contamination of the membrane layer by oil, its gas flux may drop below 30 SLPM.

[0051] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. An oil-resistant special gas filtration alumina ceramic membrane and a preparation method thereof, characterized in that: The steps include: (1) mixing an alumina ceramic powder having an average particle size of 300-800 nm with a nano-titanium oxide dispersion having a concentration of 12-15 wt%, and reacting the mixture under high pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 h, wherein the average particle size of the nano-titanium oxide in the nano-titanium oxide dispersion is 5-20 nm; (2) drying the material obtained in step (1), and then performing low-temperature sintering at 420-430° C. for 25-35 min using a microwave heating device to obtain titanium oxide-coated aluminum oxide powder; (3) ball-milling the titanium oxide-coated alumina powder obtained in step (2), PVA with an average particle size of 0.8-1.2 μm, RO water, a polysiloxane defoamer and a methyl cellulose thickener to mix uniformly; (4) coating the material obtained in step (3) on an oil-resistant gas filter support to obtain a wet blank; (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1150-1450° C. for 3-5 hours to obtain the oil-resistant special gas filtration alumina ceramic membrane.

2. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%.

3. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 120° C. and the drying time is 4 hours.

4. The preparation method according to claim 1, characterized in that: In the step (3), the ratio of titanium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 20-25wt%: 2.5-3wt%: 70-76wt%: 0.01-0.03%: 0.98-1.99wt%.

5. The preparation method according to claim 4, characterized in that: In the step (3), the average particle size of the PVA is 1 μm.

6. The preparation method according to claim 1, characterized in that: In the step (4), the shade drying time is 4 hours.

7. The preparation method according to claim 1, characterized in that: In the step (4), the drying temperature is 105° C. and the drying time is 2 hours.

8. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of TiO2 in the nano-titanium oxide is greater than 99.9%; in the step (3), the ratio of titanium oxide-coated alumina powder, PVA, RO water, polysilicone defoamer and methyl cellulose thickener is 20-25wt%: 2.5-3wt%: 70-76wt%: 0.01-0.03%: 0.98-1.99wt%.

9. The preparation method according to claim 8, characterized in that: In the step (3), the average particle size of the PVA is 1 μm.

10. The preparation method according to claim 9, characterized in that: In the step (4), the shade drying time is 4 hours; the drying temperature is 105° C. and the time is 2 hours.